Inosine Monophosphate Dehydrogenase (IMPDH) Activity as a Pharmacodynamic Biomarker of Mycophenolic Acid Effects in Pediatric Kidney Transplant Recipients - Fukuda, Tsuyoshi (2010)
Monitoring inosine monophosphate dehydrogenase (IMPDH) activity as a biomarker of mycophenolic acid (MPA)–induced immunosuppression may serve as a novel approach in pharmacokinetics (PK)/pharmacodynamics (PD)–guided therapy. The authors prospectively studied MPA pharmacokinetics and IMPDH inhibition in 28 pediatric de novo kidney transplant recipients. Pretransplant IMPDH activity and full PK/PD profiles were obtained at 3 different occasions: 1 to 3 days, 4 to 9 days, and approximately 6 months after transplant. Large intra- and interpatient variability was noted in MPA pharmacokinetics and exposure and IMPDH inhibition. MPA exposure (AU(C0-12 h)) was low early posttransplant and increased over time and stabilized at months 3 to 6. Mean pretransplant IMPDH activity (6.4 ± 4.6 nmol/h/mg protein) was lower than previously reported in adults. In most of the patients, IMPDH enzyme activity decreased with increasing MPA plasma concentration, with maximum inhibition coinciding with maximum MPA concentration. The overall relationship between MPA concentration and IMPDH activity was described by a direct inhibitory E(max) model (EC(50) = 0.97 mg/L). This study suggests the importance of early PK/PD monitoring to improve drug exposure. Because IMPDH inhibition is well correlated to MPA concentration, pre-transplant IMPDH activity may serve as an early marker to guide the initial level of MPA exposure required in a pediatric population.